Evaluation of the Implementation of the Payroll Accounting System at PT Astra International Daihatsu Martadinata - Thalia E. S. Kaunang; Meily Y. B. Kalalo (Indonesian Journal of Business Analytics, 2023)
Payroll Accounting System is a system designed to handle the calculation of salaries and wages of employees and their payments. PT Astra Internasional Daihatsu Martadinata is a company engaged in the automotive sector, selling vehicle products and providing repair services. This company has implemented a computerized payroll accounting system. The purpose of this study is to determine the application of the payroll accounting system at PT Astra International Daihatsu Martadinata, as well as its comparison with existing theories. The method used is descriptive qualitative. The results of the study show that a computerized payroll accounting system is quite helpful for companies in recording attendance lists, and payment of salaries is made through bank transfers to each employee's account, resulting in cost savings because the company no longer uses salaries.